Identification of a G‐Protein Subunit‐α11 Gain‐of‐Function Mutation, Val340Met, in a Family With Autosomal Dominant Hypocalcemia Type 2 (ADH2). (June 2016) - Piret, Sian E; Gorvin, Caroline M; Pagnamenta, Alistair T; Howles, Sarah A; Cranston, Treena; Rust, Nigel; Nesbit, M Andrew; Glaser, Ben; Taylor, Jenny C; Buchs, Andreas E; Hannan, Fadil M; Thakker, Rajesh V
ABSTRACT: Autosomal dominant hypocalcemia (ADH) is characterized by hypocalcemia, inappropriately low serum parathyroid hormone concentrations and hypercalciuria. ADH is genetically heterogeneous with ADH type 1 (ADH1), the predominant form, being caused by germline gain‐of‐function mutations of the G‐protein coupled calcium‐sensing receptor (CaSR), and ADH2 caused by germline gain‐of‐function mutations of G‐protein subunit α‐11 (Gα11 ). To date Gα11 mutations causing ADH2 have been reported in only five probands. We investigated a multigenerational nonconsanguineous family, from Iran, with ADH and keratoconus which are not known to be associated, for causative mutations by whole‐exome sequencing in two individuals with hypoparathyroidism, of whom one also had keratoconus, followed by cosegregation analysis of variants. This identified a novel heterozygous germline Val340Met Gα11 mutation in both individuals, and this was also present in the other two relatives with hypocalcemia that were tested. Three‐dimensional modeling revealed the Val340Met mutation to likely alter the conformation of the C‐terminal α5 helix, which may affect G‐protein coupled receptor binding and G‐protein activation. In vitro functional expression of wild‐type (Val340) and mutant (Met340) Gα11 proteins in HEK293 cells stably expressing the CaSR, demonstrated that the intracellular calcium responses following stimulation with extracellular calcium, of the mutant Met340 Gα11 led to a leftward shift of the concentration‐response curve with a significantly ( p  < 0.0001) reduced mean half‐maximal concentration (EC50 ) value of 2.44 mM (95% CI, 2.31 to 2.77 mM) when compared to the wild‐type EC50 of 3.14 mM (95% CI, 3.03 to 3.26 mM), consistent with a gain‐of‐function mutation. A novel His403Gln variant in transforming growth factor, beta‐induced (TGFBI), that may be causing keratoconus was also identified, indicating likely digenic inheritance of keratoconus and ADH2 in this family. In conclusion, our identification of a novel germline gain‐of‐function Gα11 mutation, Val340Met, causing ADH2 demonstrates the importance of the Gα11 C‐terminal region for G‐protein function and CaSR signal transduction. © 2016 American Society for Bone and Mineral Research.